2000
DOI: 10.1177/00131640021970952
|View full text |Cite
|
Sign up to set email alerts
|

Life Event Checklists: Revisiting the Social Readjustment Rating Scale after 30 Years

Abstract: Despite criticism, the Social Readjustment Rating Scale (SRRS) is one of the most widely cited measurement instruments in the stress literature. This research assesses several criticisms of the SRRS after years of widespread use. Specifically, the authors evaluate content-related criticisms, including differential prediction of desirable relative to undesirable life events, controllable relative to uncontrollable life events, and contaminated relative to uncontaminated life event items. On balance, the authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(141 citation statements)
references
References 23 publications
2
134
1
4
Order By: Relevance
“…This scale is widely used in the literature and was judged to be a good measure of life events in a review assessing its use over 30 years of research (Scully et al, 2000) and the adult version has test-retest reliability of r=.71 over a six week period (Horowitz et al, 1977). It gathers information about stressful life events that have happened in the last year such as death or divorce of parents, changes in acceptance by peers, and hospitalisation of a sibling.…”
Section: Participantsmentioning
confidence: 99%
“…This scale is widely used in the literature and was judged to be a good measure of life events in a review assessing its use over 30 years of research (Scully et al, 2000) and the adult version has test-retest reliability of r=.71 over a six week period (Horowitz et al, 1977). It gathers information about stressful life events that have happened in the last year such as death or divorce of parents, changes in acceptance by peers, and hospitalisation of a sibling.…”
Section: Participantsmentioning
confidence: 99%
“…17 Yet, existing studies that have specifically assessed housing instability over the [2007][2008][2009] recession and alcohol problems have yielded ambiguous results. Data from the previously mentioned Michigan Recession and Recovery Study showed that no forms of housing instability other than homelessness (AOR, 3.05; 95%CI, 1.03, 11.6) were significantly associated with harmful alcohol use at pG0.05.…”
Section: Introductionmentioning
confidence: 99%
“…Očito je da sama ličnost, upitnički operacionalizovana u skladu sa reformulisanim Grejovim modelom, nije dovoljna da bi se valjano objasnilo ponašanje osobe pod uticajem stresora. Kao prvo, naša je pretpostavka da bi sistematizacijom stresora nekom objektivnom merom, recimo starom ali pouzdanom Holmes-Raheovom skalom životnih događaja (Scully et al, 2000) ili nekom sličnom merom došlo do drugačijih rezultata u kontekstu nekorigibilnih životnih događaja. Sa druge strane, obezbeđivanjem mere kognitivne efikasnosti, usuđujemo se reći inteligencije ili npr.…”
Section: Zaključciunclassified